Implementation of mind mapping learning model through brainstorming technique in improving student’s reasoning power in catholic religious education learning grade XI phase F - Sihotang, Din Oloan; Tarigan, Egalita (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the implementation of the Mind Mapping learning model through brainstorming techniques in enhancing students' reasoning skills in Catholic Religious Education learning for Grade XI Phase F. The research method used is Classroom Action Research (CAR) with two cycles. The research subjects were Grade XI students in a senior high school. Data were collected through observations, tests, and interviews, then analyzed descriptively using quantitative and qualitative approaches. The results indicate an improvement in students' reasoning skills from the pre-action phase to Cycle II. Before the intervention, the average mastery level was only 66%, increasing to 79% in Cycle I and reaching 87% in Cycle II. The most significant improvements were observed in students' abilities to identify, classify, draw conclusions, present evidence, and provide comprehensive statements. Thus, the Mind Mapping learning model through brainstorming techniques effectively enhances students' reasoning skills. The implications of this study suggest that interactive learning strategies can improve students' understanding and active participation in learning.